Evaluation of stAPP: a smartphone-based intervention to reduce prolonged sitting among Belgian adults. (6th September 2017) - Arrogi, Anass; Bogaerts, An; Seghers, Jan; Devloo, Karlien; Vanden Abeele, Vero; Geurts, Luc; Wauters, Jeroen; Boen, Filip
Abstract: Excessive uninterrupted sitting, also known as sedentary behavior, has been detrimentally associated with several health outcomes. However, the general population is often unaware of these health risks. Mobile phone technology offers great potential to increase awareness and to initiate behavior change. This study examined the short-term effects of stAPP, a smartphone-based intervention, on prolonged sitting behavior. Fifty-eight participants were randomly assigned to an intervention group (IG, n = 31) or a control group (CG, n = 27). After 1 week of baseline assessment, the IG received stAPP (i.e. smartphone, smartphone app and corresponding motion sensor) and used it during the following week. CG participants were monitored during 2 weeks without receiving stAPP. Total daily sitting time and prolonged sitting bouts (>30 min bouts of sitting) were objectively assessed using activPAL3 inclinometers. Although no significant changes emerged in the CG in any of the sitting parameters, total sitting time (on weekdays; p = 0.032), number of prolonged sitting bouts (>30 min of sitting) [both on week- ( p < 0.001) and weekend days ( p = 0.008)] and average duration of prolonged sitting bouts [both on week- ( p = 0.004) and weekend days ( p = 0.029)] decreased significantly in the IG. The stAPP smartphone-based intervention constitutes a promising intervention tool to interrupt and reduce prolonged sitting behavior. Further long-term studies on a larger scale are needed to further explore the effectiveness of a smartphone-based intervention aimed at reducing prolonged sitting behavior.